(untitled) (Journal of history, 2020)
In this review article, the author highlights the history of publications of the Tuvan fairy tale “Bogda Changar Khan” in Mongolia and China. This tale we refer to the independent Tuvan epic tradition of the epic “Jangar”. Undoubtedly, thanks to the recording and publication of Tuvan scientist Kuular Dorzh Sengilovich, the fairy tale “Bogda Changar Khan” attracted the attention of scientists studying Jangar not only in our country but also in neighboring countries. Thus, D. S. Kuular in 1973 in the XI issue of the series Philology of the Kalmyk research Institute of language, literature and history published a subscript Russian translation of “Bogda Changar Khan”. Just five years later, in 1978, the Tuvan fairy tale is translated and published by the Academy of Sciences of Mongolia. In 2010, Inner Mongolia University (China) published “Bogda Changar Khan” on the old Mongolian script – khudam bichig. Since the introduction of the text into scientific circulation in these countries, there are also scientific works on “Bogda Changar Khan” and devoted to two Tuvan legends “Kongar-Baadai” and “Kongar-Maadyr”.